The yellow lantern [large type] - Dicken, Angie (True colors, 2019)
"In 1824, Josephine Clayton is considered dead by everyone in her Massachusetts village--especially the doctor she has assisted for several months. Yet, she is still very much alive. After the doctor's illegal dealing with his body snatcher to obtain her body, Josephine awakens, positioned as the next corpse for his research. To cover up his crime, the doctor tries to kill her, but Josephine begs to be spared. They strike a deal--Josephine will leave her village and work at a distant cotton mill. All the while, she'll await her true mission--posing as a mourner to help the body snatcher procure her replacement. At the mill though, Josephine is praised for her medical remedies among the other female workers, gaining attention from the handsome factory manager, Braham Taylor. Yet, when Braham's own loved one becomes the prey for the next grave robbing, Josie must make a choice that could put her dark past behind her or steal away the promise of any future at all"--